Achieving sustainable green agriculture: analyze the enabling role of data elements in agricultural carbon reduction - Lidong Shi; Jiahui Zhao; Xinyi Du; Yuntao Tan; Ting Lei; Ming Xu; Ming Xu; Yang Shen (Frontiers in Earth Science, 2025)
IntroductionControlling agricultural carbon emissions is an important part of promoting the green development of agriculture. This paper explores the relationship between data elements (DE) and agricultural carbon emissions (ACE), which is an important manifestation of achieving green emission reduction and sustainable agricultural development in agriculture.MethodsBased on the empirical data of 30 provinces in China from 2012 to 2022, this paper evaluated the influence between the two by using the fixed effects model and the mediating effects model, and explored the heterogeneous effects in geographical location and grain production areas.ResultsFirst, data elements have a significant inhibitory effect on agricultural carbon emissions. Second, data elements have obvious heterogeneity in agricultural carbon emissions. Thirdly, fintech and land use play a significant mediating role in the impact of data elements on agricultural carbon emissions.DiscussionThis paper not only enriches the theoretical research on the impact of data elements on agricultural carbon emissions, but also provides corresponding empirical evidence. It offers significant reference for deepening the green development reform of industry, optimizing the allocation of human resources, promoting high-quality agricultural development, and achieving rural revitalization in China.